2013
DOI: 10.1016/j.anbehav.2013.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Parasitoid infestation changes female mating preferences

Abstract: Females often adjust their mating preference to environmental and social conditions. This plasticity of preference can be adaptive for females and can have important consequences for the evolution of male traits. While predation and parasitism are widespread, their effects on female preferences have rarely been investigated. Females of the cricket Gryllus lineaticeps are parasitized by the parasitoid fly Ormia ochracea. Infestation with fly larvae substantially reduces female life span and thus reproductive op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…According to Lopez (1998) energetic costs related to infection may prohibit females from more energy-consuming discriminatory mate choice. A similar disease-dependent pattern of mate preferences was reported in female crickets Gryllus lineaticeps ( Beckers & Wagner, 2013 ), where parasitized females showed no preferences towards males with attractive male characteristics ( Beckers & Wagner, 2013 ). The authors suggested that in life-threatening situations, mate selection criteria are less strict to facilitate rapid reproduction.…”
Section: Introductionsupporting
confidence: 70%
“…According to Lopez (1998) energetic costs related to infection may prohibit females from more energy-consuming discriminatory mate choice. A similar disease-dependent pattern of mate preferences was reported in female crickets Gryllus lineaticeps ( Beckers & Wagner, 2013 ), where parasitized females showed no preferences towards males with attractive male characteristics ( Beckers & Wagner, 2013 ). The authors suggested that in life-threatening situations, mate selection criteria are less strict to facilitate rapid reproduction.…”
Section: Introductionsupporting
confidence: 70%
“…As a result, females may adjust their choosiness based on their ability to afford perceived search costs. Many studies have manipulated the costs of choosiness and have found that females adjust choosiness in response to changes in a variety of factors such as parasitism (Beckers & Wagner, 2013), age (Richard, Lecomte, De Fraipont, & Clobert, 2005;Ronald, Fern andez-Juricic, & Lucas, 2012), body condition and diet (Hebets, Wesson, & Shamble, 2008;Moskalik & Uetz, 2011;Vitousek, 2009), predation (Karino, Kuwamura, Nakashima, & Sakai, 2000;Willis, Rosenthal, & Ryan, 2012), male density and trait variability (Fowler-Finn & Rodríguez, 2012a;Lehmann, 2007), and previous experiences with certain male phenotypes (FowlerFinn & Rodríguez, 2012b;Hebets, 2003;Wagner, Smeds, & Wiegmann, 2001). …”
mentioning
confidence: 98%
“…This finding correlates with the sexual immune dimorphism in the system, where males have a more efficient immune response than females (Roth et al 2011). The plasticity of mate preference upon immune activation of males and females is still poorly understood (Beckers and Wagner 2013). It is becoming clear, however, that a change in the strength of mate preference in response to condition can have severe implications for the evolution of secondary sexual traits (Cotton et al 2006).…”
Section: Mate Preference Of Unchallenged Fishmentioning
confidence: 76%
“…Upon immune challenge, females might invest more resources into the current reproduction event as a last-ditch attempt to increase their reproductive success (Rolff 1999;Pfennig and Tinsley 2002;Roth et al 2012b;Beckers and Wagner 2013). Previous results already indicate that challenged females produce larger offspring with an induced immune defense compared to offspring of unchallenged females (Roth et al 2012b).…”
Section: Mate Preference Of Immune-challenged Fishmentioning
confidence: 87%
See 1 more Smart Citation